2023
DOI: 10.1002/vetr.2644
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A does not predict non‐survival in hospitalised adult horses with acute colitis

Abstract: Background Predicting non‐survival in horses with acute colitis improves early decision making. Therefore, this study aimed to determine the prognostic value of serum amyloid A (SAA) and other clinicopathological and clinical variables in adult horses with acute colitis. Methods Clinical variables, SAA and other blood biomarkers, including plasma L‐lactate (lactate), were assessed in 176 horses with acute colitis. A multivariate model for the prediction of non‐survival was constructed. Icelandic horses were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…In numerous circumstances, SAA rose; as [7] noted, in colic, it rose in reaction to pain. Studies have demonstrated that serum amyloid A (SAA) is a useful predictive too, since horses with increased SAA upon admission exhibit worse survival rates [19]. The most sensitive variable evaluated in relation to the need for surgical intervention or the emergence of complications in horses exhibiting symptoms of acute abdominal pain was SAA concentration, according to the current study's results [6].…”
Section: Discussionmentioning
confidence: 80%
“…In numerous circumstances, SAA rose; as [7] noted, in colic, it rose in reaction to pain. Studies have demonstrated that serum amyloid A (SAA) is a useful predictive too, since horses with increased SAA upon admission exhibit worse survival rates [19]. The most sensitive variable evaluated in relation to the need for surgical intervention or the emergence of complications in horses exhibiting symptoms of acute abdominal pain was SAA concentration, according to the current study's results [6].…”
Section: Discussionmentioning
confidence: 80%
“…This study by Kira Runge and co‐workers in Denmark aimed to determine the prognostic value of serum amyloid A (SAA) and other clinicopathological and clinical variables in adult horses with acute colitis .…”
Section: Acute Colitis Survivalmentioning
confidence: 99%
“…This retrospective multicentre investigation is the most extensive study describing horses with acute diarrhoea and the first comparing clinical, laboratory and epidemiologic findings across different geographic regions. Previous studies have focussed on cases from either one institution, 5,6,8,11 one geographic location 4,16 or one country. 2,17 In line with previous reports, 2,4,11,17 horses with acute diarrhoea comprised a low to moderate percentage of the total caseload ranging between 0.1% and 7.2%, with the highest rates reported in a university from Colombia and one from Mexico.…”
Section: Factors Associated With Survivalmentioning
confidence: 99%
“…1 Most studies on equine colitis have focussed on the factors associated with mortality at single facilities involving fewer than 150 horses. [3][4][5][6][7][8] The true incidence of colitis in horses is difficult to determine from those studies; however, these studies have identified several risk factors associated with mortality. Specifically, age, a history of antimicrobial therapy, tachycardia, haemoconcentration, hypoproteinaemia and the development of azotemia during hospitalisation were all associated with mortality in horses with diarrhoea.…”
Section: Introductionmentioning
confidence: 99%